Endogenous Maternity Allowances as Exemplified by Academic Promotion Standards - Heinrich Ursprung (Center for Economic Studies and ifo Institute (CESifo), 2019)
I model the strategic interaction between scientists aiming for promotion and a research institution that seeks a highly productive faculty by setting a maternity allowance in the form of a minimum promotion standard. The model shows that maternity allowances need not derive from moral justice arguments but can emerge endogenously from efficiency considerations. The underlying mechanism rests on the assumption that exceptionally productive female professionals are also exceptionally productive if they choose to become mothers. Even though motherhood temporarily handicaps their productivity, it is exactly this cost of motherhood that signals the mothers' intrinsic high productivity. I explicitly refer to the academic labor market and use empirical evidence from academia to justify the model's specification, but the conclusions carry over to promotion decisions at the executive level in most professional lines of occupation.
Keywords: C72; D82; J13; J16; M14; M51; 330; maternity; job market signaling; fertility; research productivity; highly skilled labor; economics of science; scientometrics